Activated Protein C Inhibits Lipopolysaccharide-Induced Tumor Necrosis Factor-α Production by Inhibiting Activation of both Nuclear Factor-κB and Activator Protein-1 in Human Monocytes - Yuksel, Mehtap; Okajima, Kenji; Uchiba, Mitsuhiro; Horiuchi, Seikoh; Okabe, Hiroaki (Thrombosis and Haemostasis, 2002)
Activated protein C (APC), an important natural anticoagulant, inhibits tumor necrosis factor-α (TNF-α) production and attenuates various deleterious events induced by lipopolysaccharide (LPS), contributing thereby to a significant reduction of mortality in patients with severe sepsis. In this study, we investigated the mechanism(s) by which APC inhibits TNF-α production by LPS-stimulated human monocytes in vitro. Although APC inhibited LPS-induced TNF-α production in a concentration-dependent fashion, diisopropyl fluorophosphate-treated APC, an active-site-blocked APC, had no effect. APC inhibited both the binding of nuclear factor-κB (NF-κB) to target sites and the degradation of IκBα. APC also inhibited both the binding of activator protein-1 (AP-1) to target sites and the activation of mitogen-activated protein kinase pathways. These observations strongly suggest that APC inhibited LPS-induced TNF-α production by inhibiting the activation of both NF-κB and AP-1 and that the inhibitory activity of APC might depend on its serine protease activity. These results would at least partly explain the mechanism(s) by which APC reduces the tissue injury seen in animal models of sepsis and in patients with sepsis.
Keywords: Activated protein C; human monocytes; TNF-α; NF-κB; AP-1